PENGARUH SUHU PEMBAKARAN ABU AMPAS KOPI SEBAGAI BAHAN SUBTITUSI PARSIAL SEMEN TERHADAP NILAI KUAT TEKAN MORTAR - Muda, Jenny Suwa; firdaus, Firdaus (Jurnal Tekno, 2023)
The rest of the coffee harvest or coffee grounds are often not widely used by the community, even though the rest of the coffee harvest can still be used for various purposes, one of which is as a substitute for cement where coffee is a ponzolan material because it contains silica such as cement. The large number of leftover coffee harvests and the ease of obtaining these waste materials in large quantities allow it to be used as an alternative material to substitute cement. The purpose of this study was to determine the optimal temperature substitution of coffee grounds ash in cement against the compressive strength of Mortar with a temperature ratio of 400⁰C, 500⁰C and 600⁰C and to find out what the optimal composition of coffee grounds ash substitution with the ratio of the test object as much as 3 ratios 10%, 15% and 20% with a comparison of 3 specimens each at the age of testing for compressive strength of 7, 14, 21 and 28 days. Based on the test results of ages 7, 14, 21 and 28 days at a temperature of 400⁰C, 500⁰C and 600⁰C, the optimum value of the best combustion temperature is at 400⁰C and the best substitution mixture composition variation is 10% of coffee grounds ash mixture.